2020
DOI: 10.1016/j.jaccas.2020.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Papillary Muscle Rupture Due to Delayed STEMI Presentation in a Patient Self-Isolating for Presumed COVID-19

Abstract: A 57-year-old man acutely developed chest tightness and dyspnea. Given concern that his symptoms were consistent with COVID-19, the patient self-isolated. After 1 week of worsening symptoms, the patient presented with hypoxia and hypotension. He was found to have an occluded right coronary artery and ruptured posteromedial papillary muscle. ( Level of Difficulty: Beginner. )

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…[ 177 ] However, case studies showed that delayed STEMI presentation may have increased the risk of mechanical complications associated with AMI. [ 179 ] The European Society of Cardiology (ESC) recommends a maximum delay from STEMI presentation to reperfusion of less than 120 minutes for COVID-19 patients. Although non-STEMI ACS is an urgent condition, emergent PCI is usually not necessary.…”
Section: Cardiac Disease and Sars-cov-2 Infectionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 177 ] However, case studies showed that delayed STEMI presentation may have increased the risk of mechanical complications associated with AMI. [ 179 ] The European Society of Cardiology (ESC) recommends a maximum delay from STEMI presentation to reperfusion of less than 120 minutes for COVID-19 patients. Although non-STEMI ACS is an urgent condition, emergent PCI is usually not necessary.…”
Section: Cardiac Disease and Sars-cov-2 Infectionmentioning
confidence: 99%
“…These drops were associated with multiple factors, including reduced numbers of hospital visits due to patient reluctance, increased medical reperfusion, reduced daily stressors due to social distancing and quarantine, less pollution from traffic and factories, more rest and fewer activities, and, perhaps, less smoking due to warnings from social media [177] . However, case studies showed that delayed STEMI presentation may have increased the risk of mechanical complications associated with AMI [179] . The European Society of Cardiology (ESC) recommends a maximum delay from STEMI presentation to reperfusion of less than 120 minutes for COVID-19 patients.…”
Section: Cardiac Disease and Sars-cov-2 Infectionmentioning
confidence: 99%
“…( 19 ) present a series of patients with delayed presentation for STEMI associated with cardiogenic shock on presentation. Kunkel and Anwaruddin ( 20 ) describe a patient with delayed presentation of inferior STEMI that resulted in papillary muscle rupture and severe mitral regurgitation which required emergency surgical intervention. Yousefzai and Bhimaraj ( 21 ) present a patient who was misdiagnosed with presumed COVID-19 infection but who actually had an acute coronary syndrome.…”
mentioning
confidence: 99%
“…43 Yet, it is this group of individuals, in whom cardiovascular disease is most prevalent, 44 that will have been disadvantaged the most from delays in receiving timely diagnosis and treatment. 45 For instance, surges in mechanical complications following ACS have been described during the pandemic, with reports of ventricular septal and free wall rupture, 46 , 47 acute functional mitral regurgitation, 48 and cardiogenic shock not seen in such frequency since prior to the establishment of primary PCI networks. 49…”
Section: Discussionmentioning
confidence: 99%